2006
DOI: 10.1038/sj.onc.1209437
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor p16Ink4a regulates T lymphocyte survival

Abstract: In contrast to other cell cycle inhibitors, the tumor suppressor p16 Ink4a is not detectable or expressed at very low levels in embryonic and adult mouse tissues, and therefore it has often been considered as a specialized checkpoint protein that does not participate in the control of normal cell cycle progression. However, Ink4a À/À mice possess increased thymus size and cellularity, thus suggesting the involvement of p16 Ink4a in the control of thymocyte proliferation. In this study, we found increased numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Immune cells modulate obesityinduced glucose intolerance and insulin resistance in T2D. p16 INK4a and p15 INK4b modulate T lymphocyte proliferation, senescence, and apoptosis [59][60][61]. In myeloid cells, p15 INK4b plays a role in monocyte proliferation [62].…”
Section: Cdkn2a/b and Chronic Inflammation In Diabetes And Obesitymentioning
confidence: 99%
“…Immune cells modulate obesityinduced glucose intolerance and insulin resistance in T2D. p16 INK4a and p15 INK4b modulate T lymphocyte proliferation, senescence, and apoptosis [59][60][61]. In myeloid cells, p15 INK4b plays a role in monocyte proliferation [62].…”
Section: Cdkn2a/b and Chronic Inflammation In Diabetes And Obesitymentioning
confidence: 99%
“…18 Consistent with this result, a role for p16 INK4a in peripheral T-cell replicative senescence/hypoproliferation has been proposed 19,20 because germline p16 INK4a -deficient mice have increased thymocyte and peripheral T-cell numbers. 21,22 Of particular importance to the present work, we and others have shown an accumulation of p16 INK4a expressing T cells in human peripheral blood with aging. 17,23 This expression of p16 INK4a appears to be a biomarker of physiologic as opposed to chronologic age, independently correlating with gerontogenic behaviors such as smoking and physical inactivity.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Evidence from loss-and gain-of-function studies indicates that Ink4a is an important regulator of thymopoiesis. For example, thymus size is increased in Ink4a-deficient mouse strains, 15,16 and mice engineered to express Ink4a under the control of an lck promoter have a block in T-cell differentiation at the DN3 stage. 17 More recently, Liu et al conditionally deleted Ink4a in thymocytes by mating mice with a floxed Ink4a allele to lck-Cre mice and demonstrated that thymic involution was delayed significantly.…”
Section: Introductionmentioning
confidence: 99%